Synergistic effects in magnetically recoverable nanocomposites of CuO nanoleaves with Fe3O4 nanoparticles for organic dye degradation - Londoño Calderón, César Leandro (2025)
In this work, we report the synthesis and characterization of Fe3O4/CuO nanocomposites and demonstrate their catalytic efficiency towards the degradation of organic dyes. Single-crystalline Fe3O4 nanoparticles of 11 nm were obtained via coprecipitation and functionalized with β-alanine for colloidal stability and chemical affinity towards the CuO surface. The CuO nanoleaves were produced by sonochemical precipitation, resulting in nanostructures with average sizes of 1080, 286, and 15 nm in long, wide, and thick, respectively. Moreover, the nanoleaves are polycrystalline, with an average crystallite size of 16 nm, and with band-gap energy of 1.48 eV. The nanocomposites were prepared by mixing the two nanostructures in various ratios to study the effect of the composition on both properties and technological performance. Field emission scanning electron microscopy confirmed that the ratio of primary nanostructures was retained in the nanocomposites and showed that the exposed surface area of nanoleaves decreased with an increasing percentage of Fe3O4 nanoparticles. While the crystalline structure of the primary nanostructures remained unchanged, the band-gap energy increased to 1.78 eV. These nanocomposites demonstrated impressive catalytic efficiency, achieving nearly complete degradation of methyl orange with H2O2 assisted by ultrasonication. This high catalytic activity, coupled with ease of recovery and reuse, makes these nanocomposites a promising solution for water remediation applications.